Potential effects of inhaler mouthpiece size on particle deposition in the human upper airway. Issue 9 (2nd August 2022) - Cai, Xinyu; Ma, Bingjie; Kourmatzis, Agisilaos; Salehi, Fatemeh; Lee, Ann; Farina, Dino; Chan, Kim; Cheng, Shaokoon
Abstract: Understanding the impact of inhaler mouthpiece sizes on particle transport and deposition in the human upper airway is important to optimize inhaler designs toward improving the therapeutic efficacy of inhaled drug delivery. This study demonstrates the potential effects of inhaler mouthpiece size on particle deposition in the human pharynx. MRI scans of two healthy human volunteers using a small and a large inhaler mouthpiece mockup were acquired. Four 3 D models of the pharynx were reconstructed from the MRI images, and CFD simulations using discrete phase modeling and polydisperse particles (MMD: 6.96 μm, span: 1.38 μm) were performed using two different transient flow profiles to investigate particle deposition with different peak flow rates. The results showed that particle deposition in the pharynx associated with a large mouthpiece and low peak flow rate (27 L/min) is more than 80% in one of the subjects, which is a onefold higher compared to when the subject was with the small inhaler mouthpiece. The cases with a small inhaler mouthpiece and high peak flow rate (85 L/min) have the least number of particles deposited in the upper airways of both subjects. The use of large inhaler mouthpiece results in an erratic distribution of particles deposition, with a higher concentration of particles in the oral cavity, not observed with the small inhaler mouthpiece. The results from this work provide further evidence to existing literature that inhaler mouthpiece size matters and that it produces intra and inter-individual variations in drug particle deposition characteristics in the human upper airway.